(untitled) (Journal of Education and Development, 2019)
Most of the teacher preparation programs in the United States adhere to a traditional curriculum that includes courses in foundations, liberal arts, methods, and student teaching. Too often these programs fail to provide opportunities for culturally responsive teaching where teacher candidates are encouraged to explore the role of culture in developing identity, providing space for learning, and building communities. A one-year Urban Teacher Education Program (UTEP) was created that focused on preparing teachers to work with disadvantaged, underprivileged, and marginalized children in urban schools. Teacher candidates received spaces to question their own thinking and reflect about issues related to (1) identity, (2) culture, (3) learning, and (4) assessment during this program. Four years after program completion, five participants from UTEP were selected for this study. The study used a mixed method approach to measure maintenance in transformation in their thinking. The results showed sustainability of the impact of the program four years later.